Faktor-faktor yang mempengaruhi kunjungan mahasiswa ke Perpustakaan Fakultas Kehutanan Univeritas Lancang Kuning - Eko Saputra Utama (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This study aims to determine the effect of library collections on student visits to the Faculty of Forestry Library of the University of Lancang Kuning. Type This research uses descriptive that is by collecting data obtained from respondents from the results of questionnaire answers and then the data tabulated. Sample determination was done by random sampling. While the data collection is done by survey method with questionnaire as collector of research data. The result of the research shows that the factors that influence the student visit to the library of Faculty of Forestry of the University of Lancang Kuning are Man Power (97.14%), Library Collection (92.86%), Building and Library Facility (91,43%).